The ecosystem service of sense of place: benefits for human well-being and biodiversity conservation - HAUSMANN, ANNA; SLOTOW, ROB; BURNS, JONATHAN K.; DI MININ, ENRICO (Environmental conservation, 2016)
Assessing the cultural benefits provided by non-market ecosystem services can contribute previously unknown information to supplement conservation decision-making. The concept of sense of place embeds all dimensions of peoples’ perceptions and interpretations of the environment, such as attachment, identity or symbolic meaning, and has the potential to link social and ecological issues. This review contains: (1) an evaluation of the importance of sense of place as an ecosystem service; and (2) comprehensive discussion as to how incorporating sense of place in an evaluation can uncover potential benefits for both biodiversity conservation and human well-being. Sense of place provides physical and psychological benefits to people, and has neglected economic value. The biodiversity-related experiences are essential components of the service that need to be further explored. A conceptual framework was used to explore how the existing knowledge on sense of place derived from other fields can be used to inform conservation decision-making, but further research is needed to fill existing gaps in knowledge. This review contributes to a better understanding of the role biodiversity plays in human well-being, and should inform the Intergovernmental Platform on Biodiversity and Ecosystem Services (IPBES).